2017
DOI: 10.1186/s12882-017-0735-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype variability in a large Spanish family with Alport syndrome associated with novel mutations in COL4A3 gene

Abstract: BackgroundAlport syndrome is an inherited renal disorder characterized by glomerular basement membrane lesions with hematuria, proteinuria and frequent hearing defects and ocular abnormalities. The disease is associated with mutations in genes encoding α3, α4, or α5 chains of type IV collagen, namely COL4A3 and COL4A4 in chromosome 2 and COL4A5 in chromosome X. In contrast to the well-known X-linked and autosomal recessive phenotypes, there is very little information about the autosomal dominant. In view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
2
Order By: Relevance
“…In 80%-85% of cases, AS is inherited in an X-linked manner (XLAS) and is caused by mutations in COL4A5. Additional, inheritance patterns include autosomal recessive AS (ARAS) manner, or, less commonly, autosomal dominant AS (ADAS) owing to mutations in COL4A3 or COL4A4 [19] .…”
Section: Asmentioning
confidence: 99%
See 1 more Smart Citation
“…In 80%-85% of cases, AS is inherited in an X-linked manner (XLAS) and is caused by mutations in COL4A5. Additional, inheritance patterns include autosomal recessive AS (ARAS) manner, or, less commonly, autosomal dominant AS (ADAS) owing to mutations in COL4A3 or COL4A4 [19] .…”
Section: Asmentioning
confidence: 99%
“…Cervera-Acedo et al [19] assessed a Spanish family with variable phenotypes of ADAS via clinical, histological, and genetic analyses. They reported that carriers of p.G333E and p.P1461L or p.S1492C mutations in COL4A3 presented an earlier onset of disease than individuals, who carried only the p.G333E mutation.…”
Section: Asmentioning
confidence: 99%
“…In addition, the diagnosis of XLAS is complicated, which is based on the kidney biopsy, clinical symptoms, extrarenal manifestation, and family history. Nevertheless, ∼10–15% of XLAS cases had a negative family history; those patients harbored COL4A5 de novo variants ( Lemmink et al, 1997 ; Haas, 2009 ; Cervera-Acedo et al, 2017 ; Sun et al, 2021 ). Currently, next generation sequencing (NGS) has evolved so much that with little effort and for a reasonable price, a great deal of information can be obtain.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent cause of AS is a variant in the COL4A5 gene (encoding α5 chain) located on the X chromosome, thus causing the Xlinked type of AS (XAS). Autosomal recessive AS (ARAS) or autosomal dominant type of AS (ADAS) are caused by variants in the COL4A3 or COL4A4 genes (encoding α3 or α4 chains, respectively) (1,(6)(7)(8)(9)(10)(11)(12)(13). Analysis of COL4 variants showed that XAS occurs in about one in 2000 individuals and single heterozygous COL4A3 and/or COL4A4 variants in about one in 100 (14).…”
Section: Introductionmentioning
confidence: 99%